2014
DOI: 10.1016/j.cub.2014.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Serial Dependence in the Perception of Faces

Abstract: Summary From moment to moment, we perceive objects in the world as continuous despite fluctuations in their image properties due to factors like occlusion, visual noise, and eye movements. The mechanism by which the visual system accomplishes this object continuity remains elusive. Recent results have demonstrated that the perception of low-level stimulus features such as orientation and numerosity is systematically biased (i.e., pulled) toward visual input from the recent past [1, 2]. The spatial region over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
372
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 277 publications
(425 citation statements)
references
References 35 publications
(29 reference statements)
33
372
6
Order By: Relevance
“…Second, when relative information is used as evidence to inform judgment, females tend to assimilate their judgments toward the category of the preceding faces whereas males tend to either assimilate or contrast their judgments toward or away from the category of the preceding faces, depending on the relationship between preceding and current faces. Recent studies also have reported sequential effects in the perceptual judgments of other facial domains, such as face perception (Liberman, Fischer, & Whitney, 2014), facial expression (Hsu & Yang, 2013) and facial attractiveness (Kondo, Takahashi, & Watanabe, 2012Kramer, Jones, & Sharma, 2013). With the present study, these findings suggest the inherent nature of relative judgment in face perception in general.…”
Section: Discussionsupporting
confidence: 77%
“…Second, when relative information is used as evidence to inform judgment, females tend to assimilate their judgments toward the category of the preceding faces whereas males tend to either assimilate or contrast their judgments toward or away from the category of the preceding faces, depending on the relationship between preceding and current faces. Recent studies also have reported sequential effects in the perceptual judgments of other facial domains, such as face perception (Liberman, Fischer, & Whitney, 2014), facial expression (Hsu & Yang, 2013) and facial attractiveness (Kondo, Takahashi, & Watanabe, 2012Kramer, Jones, & Sharma, 2013). With the present study, these findings suggest the inherent nature of relative judgment in face perception in general.…”
Section: Discussionsupporting
confidence: 77%
“…Such bias has been seen in a low level task, orientation judgement, in which participants' choices were significantly biased toward orientations reported in the previous trials even though the stimuli changed randomly trial-by-trial [33]. It has also been seen in a high-level task, face-perception [34]. In both cases, the effects of post-decisional processing extended to the next trial and modulated subsequent decisions.…”
Section: Biases In Post-decisional Processingmentioning
confidence: 94%
“…This is assuming that evidence is integrated without bias. However, several studies have shown that post-decisional processing could be biased, and so could distort confidence judgments [17,26,[31][32][33][34]. For example, evidence for the chosen option could be overweighed (i.e., accumulated at a larger rate than the unchosen options as in [31]) leading to an increase in confidence that is not based on objective evidence; this is known as "confirmation bias" [26].…”
Section: Biases In Post-decisional Processingmentioning
confidence: 99%
See 2 more Smart Citations